2016
DOI: 10.25110/arqvet.v19i1.2016.5785
|View full text |Cite
|
Sign up to set email alerts
|

PREVALÊNCIA DE ANTICORPOS ANTI-Leishmania infantum EM FELINOS DOMÉSTICOS FREQUENTADORES DE CLÍNICAS E HOSPITAIS VETERINÁRIOS DA CIDADE DE CASCAVEL, PARANÁ, BRASIL

Abstract: RESUMO:A Leishmaniose é uma doença protozoária grave que acomete o homem, caninos e felinos domésticos e animais selvagens, é considerada uma zoonose. Os cães domésticos são considerados os principais hospedeiros reservatórios, os felinos são considerados hospedeiros acidentais da leishmaniose, isso se deve ao fato de não haver estudos epidemiológicos e evidência experimental que comprovam que ele pode atuar como hospedeiro reservatório e disseminar a doença. O objetivo do estudo é determinar a prevalência da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
See 1 more Smart Citation
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
“…In Brazil, studies on FeL using serological, parasitological, and molecular methods revealed that infection frequencies varied from 0% to 54% (BRESCIANI et al, 2010;VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SILVA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;MENDONÇA et al, 2017;COURA et al, 2018;MATOS et al, 2018). Only a small fraction of these studies was performed in the Northeast region that was home to 82.5% of all reported cases of human leishmaniasis in Brazil between 1980 and 2005, making this region an area of epidemiological relevance for this disease in Brazil (MAIA-ELKHOURY et al, 2008;SILVA et al, 2014;MENDONÇA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%